Strategi Perpustakaan dalam Mewujudkan Layanan Prima bagi Pemustaka di Perpustakaan Universitas Potensi Utama Medan - Rahman, Idzhari; Wahyuni, Linda; Novita Sari, Rita (Universitas Sebelas Maret Library, 2023)
Excellent service through information service sources in the library is the main focus of activities in the library. Activities in the library are a benchmark for the success or decline of excellent service in the library. Library policy in developing services is one of the library's efforts to bring information sources closer to users. This study used a qualitative research method, namely field research. With the development of a library that has an information technology base, both from a library management information system and a digital library, it will provide convenience to users and convenience for librarians. Technology is able to solve the problems librarians face in their daily work. New ideas that librarians have to improve excellent service at the Potensi Utama University Library must continue to be developed. This study concludes that excellent service at the Potensi Utama University Library Medan is able to bring users closer to librarians in finding sources of information.